Economic Development and Community Vitality : A Report on Federal Funding Streams Available to the English-speaking Community of Quebec - Quebec Community Groups Network (QCGN); Community Economic Development and Employability Corporation (CEDEC); Youth Employment Services (YES) (2023)
The following report provides an overview of the main federal funding streams for the English-speaking community in Quebec (ESCQ) along with the French-speaking community in the rest of Canada. This includes an overview and analysis of the Canada Economic Development for Quebec Regions (CED-Q), including the Official Languages Economic Development Initiative (EDI) and other official language minority communities (OLMCs) specific funding streams: Regional Economic Growth through Innovation (REGI), the Quebec Economic Development Program (QEDP), and the Community Futures Program (CFP). As a means of comparing funding levels for the French-speaking community outside of Quebec, this study also reviews Canada Economic Development for the Rest of Canada (CED-ROC).
Keywords: Official Language Minority Community (OLMC)

CEDEC hopeful Official Languages Act Action Plan will have long-term impact and meaningful difference to ESCQ vitality - Community Economic Development and Employability Corporation (CEDEC) (2023)

Canada, Bilingualism and Trade - Arcand, Alan; The Conference Board of Canada (Community Economic Development and Employment Corporation (CEDEC), 2013)
The French language is one of the world’s major languages. According to L’Organisation internationale de la Francophonie (OIF), at least 220 million people in the world speak French. It’s the official language of all United Nations agencies and a large number of international organizations. The language originated in France and spread by way of the country’s overseas expansion. Today, some 30 countries in the world, including Canada, have recognized French as an official language.

Ancestors : Life, Death, and Descendants of Quebec City's Anglophones - Morrin Centre (2008)
Quebec City’s cemeteries have lots to say about our ancestors and the past. They are places of remembrance for those close to the departed, but they are also a storehouse of memories for the whole community. Cemeteries are closely linked to religious belief : They express a particular vision of the world, a set of values and a culture.

Building the City : The Influence of English Speakers on Quebec City's Architecture - Morrin Centre (2008)
Quebec City is praised for its quintessential Frenchness, yet a closer look at its architecture reveals a city with a strong British influence. Ninety-five per cent of the city was built or modified after the British conquest in 1759. In the middle of the ninete nth century, half the people in the Upper Town were English speakers, and they left a clear mark on the built environment. Many of the city’s important landmarks, from the Château Frontenac to the Price Building, were designed by English-speaking architects.

People and Faith : The Religious Life of English Speakers in Quebec City - Morrin Centre (2008)
Through this tour, you’ll learn about Quebec City’s anglophones through their places of religious worship and practice. We’ll look at distinctions between different forms of belief and you’ll gain a better understanding of Quebec’s religious landscape.

People of the River : Anglophone Life on the St. Lawrence - Morrin Centre (2008)
The Greek historian Herodotus summed up Egypt’s dependence on its great river by calling the country a “gift of the Nile.” In the same way, it could be said that Quebec is a gift of the St. Lawrence. The St. Lawrence was the “boulevard” of the territory’s first inhabitants, the Aboriginal people. Then it became the access route for French explorers. Samuel de Champlain thought it was a route to China, and this was a determining factor in his decision to found a colony at Quebec.

Rediscover Quebec City's Anglo Heritage Through Four Self-Guided Tours / Redécouvrez le visage anglophone de Québec à l'aide de quatre visites autoguidées - Morrin Centre (2008)

Earn While you Learn Sutton : A CEDEC Collaboration Story - Community Economic Development and Employability Corporation (CEDEC)
Tourism is a major economic driver in the Sutton area, however, labour shortages are hampering growth. Through innovative skills training, tourism sector employers are attracting new talent and through upskilling they are retaining and promoting their existing workforce to take on new responsibilities and secure year-round employment.